Correlation analysis of serum IL1RL1, DAPPER5, and MFGF with poor prognosis in patients with heart failure: Serum IL1RL1, DAPPER5, and MFGF in prognosis of heart failure - Yu, Cheng; Cao, Suyan; Zhang, Ying; Zhao, Yuyu; Dong, Menghao; Liu, Yulong (Journal of Medical Biochemistry, 2026)
Objective To explore the predictive value of the combined effect of serum Interleukin-1 Receptor-like 1 (IL1RL1), Dishevelled-associated protein 5 (DAPPER5), and Metabolic fibroblast growth factor (MFGF) on poor prognosis in patients with heart failure with preserved ejection fraction (HFpEF). Methods The study group consisted of 382 HFpEF patients who were diagnosed and treated at this facility between July 2023 and August 2025. The control group consisted of 382 additional healthy people who were examined physically in the same hospital over the same time period. Patients were monitored for a year following their release from therapy. The poor prognosis group comprised patients who had adverse cardiovascular events throughout the follow-up period, while the good prognosis group included the remaining patients. Each research participant’s serum levels of IL1RL1, DAPPER5, and MFGF were assessed using an enzyme-linked immunosorbent assay. Using multivariate logistic analysis, the factors influencing the poor prognosis of HFpEF patients were investigated. A receiver operating characteristic (ROC) curve was developed to evaluate the predictive significance of serum IL1RL1, DAPPER5, and MFGF independently and in combination for a poor prognosis in patients with HFpEF. Results While the study group’s serum DAPPER5 level was lower than the control group’s, the study group’s serum IL1RL1 and MFGF levels were higher. There was a statistically significant change (P<0.05). When comparing the serum levels of IL1RL1 and MFGF in individuals with varying grades of cardiac function, Grade II patients had considerably lower levels than both Grade III and Grade IV patients (P<0.05). In comparison to Grade III and Grade IV patients, participants with Grade II cardiac function showed considerably greater serum levels of DAPPER5 (P<0.05). Patients in the group with a poor prognosis were 136, while those in the group with a favorable prognosis were 246. The percentage of patients with grade IV cardiac function and the levels of serum IL1RL1, MFGF, red cell volume distribution width (RDW), and serum creatinine (Scr) were all higher in the bad prognosis group, although the level of serum DAPPER5 was lower in the good prognosis group. Multivariate logistic regression analysis revealed that while elevated DAPPER5 levels were protective factors for poor prognosis in patients with HFpEF (P<0.05), risk factors for poor prognosis included cardiovascular function grade IV, elevated RDW, and elevated levels of Scr, IL1RL1, and MFGF. The results of the ROC curve analysis showed that the combined prediction of the three indicators for poor prognosis in patients with HFpEF had an area under the curve (AUC) of 0.950, which was higher than the AUC of serum IL1RL1, DAPPER5, and MFGF alone (Z = 2.682, 2.706, and 2.714; all P < 0.05). Conclusion While DAPPER5 levels were significantly lower in patients with HFpEF, serum levels of IL1RL1 and MFGF were significantly higher. When all three indications are detected together, there is some clinical utility in predicting the poor prognosis of patients with HFpEF.